2014
DOI: 10.1371/journal.pone.0096072
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Neutrophil-to-Lymphocyte Ratio in Primary Liver Cancer: A Meta-Analysis

Abstract: The neutrophil-to-lymphocyte ratio (NLR) is a useful biomarker that reflects systemic inflammation responses. However, the prognostic value of the NLR in patients with primary liver cancer (PLC) remains controversial. We performed a meta-analysis of 26 studies (comprising 4,461 patients) to evaluate the association between the pre-treatment NLR and clinical outcomes of overall survival (OS) and disease-free survival (DFS) in patients with PLC. The correlation between NLR and tumor characteristics or other infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 43 publications
4
99
1
5
Order By: Relevance
“…We set the optimum NLR threshold value as 5, as in previous reports of other cancers. 34 Of 105 patients, 82 (78%) patients had an NLR of < 5. The median OS after resection in the patients with an NLR of < 5 was 14 months, and the median OS of those with an NLR of ≥ 5 was 5 months (p = 0.01 according to the log-rank test; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We set the optimum NLR threshold value as 5, as in previous reports of other cancers. 34 Of 105 patients, 82 (78%) patients had an NLR of < 5. The median OS after resection in the patients with an NLR of < 5 was 14 months, and the median OS of those with an NLR of ≥ 5 was 5 months (p = 0.01 according to the log-rank test; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous studies of advanced cancers, elevated NLR was a strong prognostic factor. 4,8,11,13,14,16,19,22,27,34 The role of the host inflammatory response in determining tumor spread is increasingly recognized. The association between elevated NLR and poor prognosis has several possible explanations.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that neutrophils, a key inflammatory cell type, can be mobilized and recruited to tumors. In fact, aberrant accumulation of neutrophils has been documented in a wide variety of tumors and is often associated with poor clinical outcomes (4)(5)(6)(7)(8)(9)(10)(11). Emerging evidence also suggests that neutrophils, in response to signals derived from cancer cells or stromal cells, can alter their phenotypes and migration routes and also release factors that act on tumor cells and other cell types (e.g., endothelial cells and immune cells), which we review in the following sections.…”
Section: Introductionmentioning
confidence: 99%
“…IBD is also characterized by microbiome and environmental factors which are still poorly understood. Some researchers have suggested that the systemic inflammatory response may modulate the host microbiome of IBD, and has received increased attention [23,24]. Lots of studies have indicated that effective and efficient therapy could significantly control clinical symptoms (extraintestinal manifestations), reduce relapse, maintain remission, and improve the quality of life [25][26][27].…”
Section: Discussionmentioning
confidence: 99%